Physician-physician handover from acute care to rehabilitation setting: A scoping review protocol - Seungjae Cho; Nancy Xi; Emma A. Bateman; Cynthia Chui; Eric Poon; Aran Bains; Patrick Fangping Yao; Meiqi Guo (PLoS ONE, 2025)
Objective The purpose of this scoping review is to map the existing evidence that describes strategies to improve handover from the acute care to rehabilitation settings. Introduction Poor handover processes have been associated with preventable errors, delays in care, and adverse patient outcomes. Effective physician-to-physician handover during transitions of care is critical to ensuring patient safety and optimizing clinical outcomes. Physician handover between acute and rehabilitation care settings is particularly complicated, as it requires transferring detailed and timely information for continuity of care for medically and/or surgically complex patients between components of healthcare systems with different cultures and goals of care. Despite numerous studies being published on handover, there has yet to be a synthesis of the existing literature that seeks to explore handovers across acute to rehabilitation settings as well as how care transitions can be improved. This scoping review aims to map the existing evidence on physician-to-physician handover from acute care to rehabilitation. Methods This review will be conducted following the Joanna Briggs Institute (JBI) framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines. A comprehensive search will be performed across the following electronic databases: MEDLINE(R) ALL (Ovid), Embase Classic + Embase (Ovid), APA PsycINFO (Ovid), Cochrane Central Register of Controlled Trials (Ovid), Emcare (Ovid), CINAHL Ultimate (EBSCO) and Web of Science (Clarivate). All rounds of screening, data extraction, and data synthesis will be conducted independently with each stage performed in duplicate. The extracted data will be summarized both quantitively with descriptive statistics and qualitatively using content analysis. Eligibility Criteria Qualitative and quantitative studies published in English that discuss physician-physician handover from acute care to rehabilitation settings will be included. All geographical areas will be considered. Case reports, case series, commentaries, protocols, opinion pieces (editorials), or abstracts from conferences will be excluded.